Necesidad de garantizar que la aplicación del procedimiento abreviado, en las personas reincidentes de delitos de hurto y robo, no vulnere los derechos: a la integridad personal y propiedad de las personas - Tocto González, Raúl Alexander (2015)
A prerequisite for obtaining the title of lawyer is a legal investigation to determine possible measures of solution to the problem of social reality. I thought suitable to carry out my research work considering the relevance of the subject matter and the contribution that I provide to the local, regional and national community in relation to the application of the abridged procedure, people repeat offenders of crimes of theft and robbery, does not infringe the rights: personal integrity and property of the people. Crime has increased with the evolution of society around the world, but on the other hand in search for solutions have been made reform after reform to the Constitution of the Republic of the Ecuador and the Comprehensive Organic Penal Code, which has not been enough to guarantee the rights: integrity staff and property of persons; but rather has been violating the rights guaranteedby allowing a recidivist offence of theft or theft person to welcome is many times wants, the abridged procedure. Currently, repeat offenders have the opportunity to turn to crime in a productive business, because they have well known that in two or three months will be free to return to his adventures. The information obtained from the review of literature and field research, allowed me to establish the need for a reform of the code of criminal procedure. For this reason, the present thesis work is oriented to reform rules in the substantive code, to guarantee the rights: personal integrity and property of the people, I will say that limiting eligibility of offenders to implementation of the fast-track procedure, it would be guaranteeing somehow these aforementioned rights